ANALISIS RASIO KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PADA PT. PERKEBUNAN NUSANTARA IV MEDAN TAHUN 2014-2016 - Amelia Rosella Girsang; Hotnida Sirait (Universitas Methodist Indonesia, 2018)
This study aims to investigate the financial performance of PT. Perkebunan Nusantara IV Medan in 2014-2016 based on the financial ratios analysis; measured by liquidity ratio, solvency ratio, activity ratio, and profitability ratio. The analysis method is descriptive quantitative approach. The results of the study are explained. PT. Perkebunan Nusantara IV Medan is expected to utilize the capital well and use the company’s assets effectively and efficiently in order to increase sales and profits. Ultimately, these will improve the financial health level and the financial performance.